The influence of time on the quality of life of patients with intestinal stoma - Salles,Valdemir José Alegre (2014)
INTRODUCTION: the changes caused by ostomy are not restricted to gastrointestinal physiology, but also affect self-esteem and body image, causing changes in family, professional, social and emotional life. OBJECTIVE: to evaluate the quality of life in ostomized patients. METHOD: a cross-sectional epidemiological study was carried out in individuals enrolled in the Valeparaíbana Ostomy Association. We analyzed thirty individuals divided into two equal groups according to the time of the stoma: group I included individuals with up to two years and, group II, those who had been ostomized for more than two years. A form was applied to evaluate the quality of life (WHOQOL-BREF). RESULTS: the acceptance of physical appearance was observed in 100% of the participants. The performance of daily activities was not limited by the use of the ostomy bag for either group and the mean occurrence of eventual negative feelings in all subjects was 40 to 60%. Regardless of the time of ostomy, those individuals who did not feel supported by family and/or spouse had a lower quality of life, with no observed association with sexual life satisfaction. CONCLUSION: patients with an ostomy for more than two years have a better quality of life.